Regulatory T cells suppress GM-CSF-producing T helper cells via IL-2 modulation to restrain immunopathology - Sara Costa-Pereira; Margit Lanzinger; Nicolás Núñez; Juan Villar-Vesga; Myrto Andreadou; Francesco Prisco; Philipp Häne; Elsa Roussel; Sinduya Krishnarajah; Rachel Chanel Lindemann; Laura Oberbichler; Frederike Westermann; et al. (Cell Reports)
Summary: Regulatory T (Treg) cells are critical for maintaining peripheral tolerance and preventing autoimmunity. Treg cell depletion or dysfunction results in fatal multiorgan inflammation linked to unrestrained effector T cell expansion. Here, we combine in vivo gene targeting and fate-mapping with high-dimensional cytometry to identify Treg cells’ steady-state function and suppressive mechanisms that prevent autoimmune inflammation and dissect the T helper (TH) cell-derived cytokines and responding cells executing tissue damage upon global loss of peripheral tolerance. We unveil that type 1 cytokines, granulocyte-macrophage colony-stimulating factor (GM-CSF) and interferon (IFN)γ, but not interleukin (IL)-17A, direct the ensuing immunopathology and mortality. GM-CSF orchestrates tissue invasion by monocytes and granulocytes and enhances their reactive oxygen species production and phagocytic capability. IL-2 modulation by Treg cells is crucial in restraining pathogenic GM-CSF-producing TH cells. Our study highlights the critical role of Treg cells and IL-2 signaling in controlling GM-CSF-producing TH cells and type 1 responses to curb phagocyte-mediated tissue destruction.